WAJAH â€œRYONENâ€ DALAM PUISI â€œBIARAâ€ KARYA A. MUTTAQIN - Setijawan, Wawan; Yulianto, Andik (Jurnal Pena Indonesia, 2017)
Poetry literature is a form of work that brings the imaginative and contemplative minds and feelings of the poet. Poetry represents the writer's thoughts and feelings expressed through the power of language language formed the physical structure and inner writers through a particular language. It is the power of language that mediates communication between poets as writers and poetry readers. Again, the nature of the poetry language does tend to be symbolic with certain symbols so that it makes the poetry have different sensations and sensations from other literary works such as short stories and novels. Often even a poet uses a game of symbolism not with words but also with numbers and other forms such as certain images or graphics to attract readers. One of the interesting poems for the branches of meaning related to other stories in the rest of the world is the poem A. Muttaqin. This poet is mengulik Ryonen's face in a particular image that will be revealed in this short article. Apparently, there is an acknowledgment on Ryonen's statement, which was later also acquired by A. Muttaqin. The behavior of a disciple with his teacher travels on an interesting journey to be understood by A. Muttaqin's poem. There are layers of pain experienced by Ryonen from the first visit, second, third, to sixth. On the seventh visit, there is a symbolization that indicates that Ryonen has reached the seventh hell, to finally arrive at the first tier of heaven. It means that "happiness" (even if he wants to accept it) has and will always smother her. The 7th and 14th stanzas can tell the story above. The meaning is strong enough implied is a kind of obsession that has always been a marker that humans are always haunted by a variety of pleasures both physical and spiritual even up in the world there. The pleasures, ranging from the rough to the subtle, the low to the high, have been depicted in the seventh and seventh-grade layers of heaven representing the seven levels of pleasure. It can be said that the world of the monastery is a heavenly world, because its atmospheric vibrations are very subtle. When a person enters a region of the sanctuary there is a certain happiness when someone is in a shopping place.